THE ANALYSIS OF VERBAL ELLIPSIS FOUND IN THE STORY BOOK OF “THE BOYHOOD OF RONGGOWARSITO” - I Putu Eka Suardana (Universitas Bali Dwipa, 2022)
This research entitled The Analysis of Verbal Ellipsis Found in The Story Book of “The Boyhood of Ronggowarsitoaimed at analyzing and classifying the classification of verbal ellipsis’s types in each text of story book entitled The Boyhood of Ronggowarsito. The primary data was taken from the English textbook ofThe Boyhood of Ronggowarsito(1991).The main theory used in this study was taken from the book entitled Cohesion in English(1975) by M.A.K Halliday and Ruqaiya Hasan. They stated that ellipsis is the omission of an item of a sentence on the assumption which an earlier sentence will make the meaning clear. They classify ellipsis into three types: nominal ellipsis, verbal ellipsis and clausal ellipsis. However, the focus of the research was only on the analysis of verbal ellipsis. The research method used in the research is qualitative research. The required data were classified and analyzed based on the classification of verbal ellipsis. Verbal ellipsis consisted of lexical verbal ellipsis and operator verbal ellipsis. The findings showed that verbal ellipsis consisted of lexical verbal ellipsis and operator verbal ellipsis, where lexical verbal ellipsis is marked by the omission of final element meanwhile, operator verbal ellipsis is marked by the omission of initial element.